America's Courts and the Criminal Justice System - Neubauer, David W. (Cengage Learning, Inc, 2008)
Open this book and step into America's court system! What's it like to be a judge? A prosecutor? A defense attorney? With Neubauer's best-selling book, you'll find out! This fascinating and well-researched text gives you the sense of being in the courthouse-of what it is like to work in and be a part of the system. This concept of the courthouse "players" illustrates each person's important role in bringing a case through the court process. Throughout the text, Neubauer highlights not only the pivotal role of the criminal courts within the criminal justice system but also the court's importance and impact on society as a whole